Impact of vascular resident involvement on operative variables and outcomes in endovascular aneurysm repair - Nicholas Reitsma, BHK; Sally H.J. Choi, MD; Gary K. Yang, PhD, MD (JVS-Vascular Insights)
Objective: Our objective was to determine how operative variables and patient outcomes differ for endovascular aneurysm repair (EVAR) done with and without trainees. Methods: A retrospective review of patients who underwent elective infrarenal EVARs with bifurcated endograft between October 1, 2017, and September 30, 2022, was carried out. The presence of vascular residents, patient demographics and comorbidities, intraoperative variables, and postoperative clinical outcomes were tabulated. Operative variables and patient outcomes were compared between cases with and without trainees using the Student t test. A multivariate analysis of fluoroscopic measures was also carried out using body mass index (BMI) as a covariate. Results: A total of 148 patients were included in the study with 53 cases taking place with trainees and 95 without. There were no statistically significant differences in patient demographics or comorbidities between the groups. Cases with trainees had significantly longer surgical time (84 ± 5 minutes vs 71 ± 3 minutes; P < .01), fluoroscopy time (19 ± 1 minutes vs 14 ± 1 minutes; P < .001), and higher volumes of contrast (86 ± 6 mL vs 72 ± 3 mL, P = .02). When correcting for body mass index, cases with trainees still had longer fluoroscopy times (P < .01). There was also a trend toward greater radiation doses with trainees (531 ± 74 mGy vs 381 ± 53 mGy; P = .10). The presence of trainees did not significantly impact patient outcomes such as mortality, length of stay, or postoperative complications. Conclusions: The presence of vascular residents at EVARs increased surgical and fluoroscopy time despite the presence of two attending surgeons. This finding should be considered when optimizing trainee education while minimizing radiation exposure and its impact on patient care.